Histological findings of ascending urinary tract infections in experimental rats caused by Proteus mirabilis - Al-Ani, Imad Matloub Dally; Al-Murayati, Hayder Y.; Salman, Mohammad O.; Ghani, Hameed M. (Scientific Publisher of India, 2011)
Proteus mirabilis has previously been shown to be capable of persisting in the rat kidney for up to 8 weeks and induces many physiological changes following a single inoculation of the urinary bladder. The present study examined kidney tissue from infected animals for evi-dence of renal damage. The earliest histologic changes seen on the 2nd and 4th days, consisted of mild cellular sloughing and edema associated with mononuclear infiltration in the me-dulla and to a lesser extent in the cortex. On the 1st and following weeks, tubular atrophy, interstitial fibrosis, and a mononuclear infiltrate had advanced in the renal parenchyma re-sulting in chronic pyelonephritis. The observed renal degenerations with a corresponding ascending bacterial infection in the intra-renal reflux suggest that Proteus mirabilis is capa-ble of producing chronic pyelonephritis in the rats after a single reflux challenge.